Postharvest Physicochemical changes in three cucumber cultivars with and without plastic film - Moreno Velázquez Delia; Cruz Romero, Wendy; García Lara Erika; Ibañez Martínez Armando; Barrios Díaz Juan Manuel; Barrios Díaz Benjamín (Revista Mexicana de Ciencias Agrícolas, 2018)
The cucumber once collected at commercial maturity, begins to experience rapid metabolic changes tending to senescence and death of tissues. Postharvest handling contributes in maintaining the quality of the product to the final consumer; within the major postharvest problems, is the loss of turgor, and other physical and chemical changes that detracts the appearance and final quality; the degradation rate of fruit has different behavior according to storage conditions, as well as driving conditions. In the present study, were evaluated postharvest qualities of three cultivars of fresh cucumber, Zapata, Constable and Lider, coated and uncoated with a commercial plastic film Cryovac® RD 45, stored for 15 days at room temperature. Every three days, was measured weight loss, total soluble solids (TSS), pH, titratable acidity, TSS, titratable acidity-TSS relationship and content of chlorophyll a, b and total. Weight loss was less than 1% in the three cultivars of cucumber with plastic film and about 8% in the three cultivars without plastic film. The titratable acidity-TSS relationship turn out not to be an indicative of quality. The Constable cucumber with plastic film remained the highest content of chlorophyll a, b and total until the end of the storage period. The Lider cucumbers with plastic film recorded the best chemical characteristics of TSS, citric acid, pH and titratable acidity-TSS relationship.